Optimalisasi Budidaya Maggot oleh Bank Sampah Dadali melalui Program MELIMPAH : Sinergi Ekonomi dan Keberlanjutan Lingkungan - Wazirul Luthfi; Andhar Lutfi; Hardian; Dedi Yahya Harahap; Anggun Intan Permata Sari (Jurnal Syntax Admiration, 2024)
The waste problem is a serious issue that can have a major impact on the environment and human life, with around 24% of waste in Indonesia not being managed, including in the city of Bekasi. One of them is household organic waste which is often disposed of carelessly without being managed first, which can cause air pollution and environmental damage. Thus, effective organic waste management, such as through the cultivation of Black Soldier Fly (BSF) maggots, offers environmentally friendly and economical solutions, so that PT Pertamina EP Zone 7 Tambun Field, in collaboration with the surrounding community, initiated a maggot cultivation program through the Dadali Waste Bank, Kalibaru Village, Bekasi, to reduce the volume of waste and increase environmental and economic sustainability.